Confirmation of genetic linkage between atopic IgE responses and chromosome 11q13. Issue 4 (April 1992) - Young, R P; Sharp, P A; Lynch, J R; Faux, J A; Lathrop, G M; Cookson, W O; Hopkin, J M
Abstract : Genetic linkage between atopic IgE responses and chromosome 11q13 (D11S97) has been previously reported in a limited number of extended families. Difficulties of phenotyping in the older family members, poor family structure in some families, and genetic heterogeneity were proposed as possible explanations for the variability in lod scores. To test this finding a second linkage study of 64 young nuclear families was undertaken and gave a two point lod score of 3.8 at theta = 0.07 (assuming theta m = theta f). A test of genetic heterogeneity in the nuclear families shows that atopic IgE responses are linked to this locus in 60 to 100% of families (approximate 95% confidence limits).